Druggability and molecular docking of essential secondary metabolites from Azadirachta indica leaf against angiotensin converting enzyme-2: Covid-19 in focus - Paul Chijioke Ozioko; Ukamaka Owohetete; Daniel Danladi Gaiya (African Journal of Pharmaceutical Research and Development (AJOPRED))
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly infectious and virulent coronavirus that arose in late 2019 and poses great risk to public health and safety. The SARS-CoV-2 utilizes peptidase, angiotensin-converting enzyme 2 (ACE2) for entrance and invasion into host cells. Thus, this study explored the in-silico druggability and molecular docking of essential secondary metabolites (ESMs) from Azadirachta indica leaf as potential inhibitors of ACE-2, a main receptor for the SARS-CoV-2 virus causing the COVID-19 pandemic. Through a literature survey and database mining of known compounds from A. indica in the National Center for Biotechnology Information (NCBI) database, 12 secondary metabolites and 5 FDA COVID-19-approved drugs were identified. The in-silico druggability and molecular docking experiments were performed using SwissADME and ADMETlab tools, and Autodock vina and UCSF Chimera respectively. Discovery Studio was used for docking visualization and analyses of ligand-target interactions. The results suggest potential candidates for further consideration. Of the 12 secondary metabolites from A. indica and 5 FDA-approved drugs identified, azadirachtin A, azadirachtin D, azadirachtin H, azadirachtin F, azadirachtin I and nimbolin, and ivermectin showed relatively poor druggability. Of the 5 FDAapproved medications for the treatment of COVID-19 under investigation, only paritaprevir was able to dock (representing 20%); while 6 out of the 12 compounds from A. indica were able to dock perfectly (representing 50%). The best docking results identified paritaprevir, desacetylnimbin, azadiradione, nimbin, nimbolide, nimbinene, and azadirone as capable of binding to ACE-2 with the lowest free energy (binding score) of -14.60, -11.88, -11.60, -12.33, -12.78, -12.58, and -11.40 kcal/mol respectively. This study indicated that desacetylnimbin, azadiradione, nimbin, nimbolide, nimbinene, and azadirone from A. indica leaf are potent inhibitors of hACE2 with high druggability potentials. Hence, they are valuable natural bioactive compounds capable of targeting ACE-2 as potential therapeutics against the SARS-CoV-2 virus causing COVID-19.